PERCEIVED VALUE, ATTITUDE TOWARDS AD, DAN PURCHASE INTENTION PADA IKLAN EMOSIONAL COCA COLA - Nizam Mohammad Andrianto (Universitas Pakuan, 2020)
Coca Cola released an emotional ad titled 'I Stand Against Name Calling' with the purpose of raising public awareness of the anti-bullying movement. This study aims to determine the ability of the emotional approach of advertising in the Coca Cola campaign section in influencing purchase intention on these products. The independent variable studied was Perceived Value, while the dependent variable in this study was Attitude Towards Ad and Purchase Intention. The research design used was a descriptive conclusive research design, and the data collection medium used was a survey/questionnaire. The finding of this study revealed that Perceived Value influences both Attitude Towards Ad and Purchase Intention, same goes with Attitude Towards Ad that has been proved to influences Purchase Intention. This study has an implication for marketer in general and Coca Cola in particular to create another emotional ad for their product line.